Scrutinizing the representations of flood disaster imagery in Emile Zola’s work - Ferdinal Ferdinal; Oktavianus Oktavianus; Djusmalinar (E3S Web of Conferences)
Educators, researchers, and scientists from various fields, including literary critics, are striving to address the impacts of climate change and disasters on human beings, as depicted in Emile Zola's work "The Flood," which illustrates human vulnerability amidst natural disasters. This research aims to explore the use of flood imagery by Emile Zola in his short story “The Flood,” highlighting the main themes and narrative of the story. The method used is an in-depth analysis of the images employed by Zola, including the depiction of the rising floodwaters and the chaos following the disaster, as well as the symbolic meanings behind these images. Research results show that Zola sharply captures the psychological warfare and emotional state of humans when facing destruction caused by natural disasters. The implications of this research indicate that the disaster imagery used by Zola plays a crucial role in enriching the narrative and provoking readers’ reflections on the relationship between humans and the uncontrollable forces of nature.